Steps of Reasoning in Children and Adolescents - Brocas, Isabelle; Carrillo, Juan D. (Journal of Political Economy, 2021)
We develop a novel graphical paradigm of a strict-dominance-solvable game to study the developmental trajectory of steps of reasoning between 8 years old and adulthood. Most participants play the equilibrium action either always or only when they have a dominant strategy. Although age is a determinant of equilibrium choice, some very young participants display an innate ability to play at equilibrium. Finally, the proportion of equilibrium play increases significantly until fifth grade and stabilizes afterward, suggesting that the contribution of age to equilibrium play vanishes early in life.